2020
DOI: 10.1042/bsr20193800
|View full text |Cite|
|
Sign up to set email alerts
|

The mechanism of hsa-miR-424-5 combining PD-1 through mTORC signaling pathway to stimulate immune effect and participate in Type 1 diabetes

Abstract: In the present study, hsa-miR-424-5p mimic plasmid and hsa-mir-424-5p inhibitor plasmid were designed and injected into rats respectively, and miRNA control plasmid was also constructed. Models of Type 1 diabetes (T1D) were built. After successful modeling, the expression of hsa-miR-424-5p in lymphocytes was analyzed by RT-PCR. The expression of protein PD-1, T-bet, CXCR3, STING in Th1 lymphocytes and content of IGF-1 in islet tissue were analyzed by flow analysis. The protein levels of SHP2, Rheb, mTORC1, Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Extensive studies have demonstrated that abnormal expression of miRNAs is associated with lipid metabolism disorder and atherosclerosis progression (Aryal et al, 2017; Feinberg & Moore, 2016). Emerging evidence suggests that miR‐424‐5p is involved in metabolic diseases, such as diabetes and obesity (Gasparotto et al, 2019; Wang et al, 2020). Interestingly, miR‐424‐5p is lowly expressed in the peripheral blood isolated from patients and rats with atherosclerosis (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have demonstrated that abnormal expression of miRNAs is associated with lipid metabolism disorder and atherosclerosis progression (Aryal et al, 2017; Feinberg & Moore, 2016). Emerging evidence suggests that miR‐424‐5p is involved in metabolic diseases, such as diabetes and obesity (Gasparotto et al, 2019; Wang et al, 2020). Interestingly, miR‐424‐5p is lowly expressed in the peripheral blood isolated from patients and rats with atherosclerosis (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that miR-424-5p is involved in metabolic diseases, such as diabetes and obesity (Gasparotto et al, 2019;Wang et al, 2020). Interestingly, miR-424-5p is lowly expressed in the peripheral blood isolated from patients and rats with atherosclerosis (Li et al, 2020).…”
Section: Mir-424-5p Is Required For Ctrp1-induced Regulation Of Foxo1...mentioning
confidence: 99%
“…hsa-miR-424-5p has been found to bind with PD-1 stimulating immune responses through the mTORC signal transduction, thus participating in the pathoetiology of type I diabetes ( 34 ). Similarly, up-regulation of miR-28 by targeting PD-1 and regulating cytokine secretion could modulate exhaustive differentiation of T cells ( 35 ).…”
Section: Mirnas and Pdcdmentioning
confidence: 99%
“…The miRNAs have an essential role in the regulation of PD‐1 expression (Figure 3d). The evaluation of miRNAs in lymphocyte‐derived from the diabetic mice model indicated that the elevated level of miR‐424‐5p has a negative correlation with the pathogenesis of type 1 diabetes by downregulating of PD‐1 (G. Wang, Yan, Zheng, & Zhang, 2020). Furthermore, miRNAs are involved in the suppression of cancer progression by decreasing the PD‐1 levels.…”
Section: Mirnas Involved In the Regulation Of T‐cell‐dependent Immunementioning
confidence: 99%